Cardiac‐specific succinate dehydrogenase deficiency in Barth syndrome. Issue 2 (23rd December 2015) - Dudek, Jan; Cheng, I‐Fen; Chowdhury, Arpita; Wozny, Katharina; Balleininger, Martina; Reinhold, Robert; Grunau, Silke; Callegari, Sylvie; Toischer, Karl; Wanders, Ronald JA; Hasenfuß, Gerd; Brügger, Britta; et al.
Abstract: Barth syndrome (BTHS) is a cardiomyopathy caused by the loss of tafazzin, a mitochondrial acyltransferase involved in the maturation of the glycerophospholipid cardiolipin. It has remained enigmatic as to why a systemic loss of cardiolipin leads to cardiomyopathy. Using a genetic ablation of tafazzin function in the BTHS mouse model, we identified severe structural changes in respiratory chain supercomplexes at a pre‐onset stage of the disease. This reorganization of supercomplexes was specific to cardiac tissue and could be recapitulated in cardiomyocytes derived from BTHS patients. Moreover, our analyses demonstrate a cardiac‐specific loss of succinate dehydrogenase (SDH), an enzyme linking the respiratory chain with the tricarboxylic acid cycle. As a similar defect of SDH is apparent in patient cell‐derived cardiomyocytes, we conclude that these defects represent a molecular basis for the cardiac pathology in Barth syndrome. Synopsis: Barth syndrome (BTHS) is a cardiomyopathy caused by defects in the biosynthesis of the mitochondrial phospholipid cardiolipin. BTHS mouse models and cardiomyocytes derived from patient stem cells unveil the defects in respiratory chain function. Cardiolipin deficiency causes a heart‐specific reorganization of the respiratory chain supercomplexes. The tricarboxylic acid cycle enzyme succinate dehydrogenase (complex II, SDH) is lost specifically in cardiac tissue. Reduced enzymatic functions of complex II and complex III cause a defect in mitochondrial respiration. The structural changes in the respiratory chain cause an increased production of reactive oxygen species in BTHS. Abstract : Barth syndrome (BTHS) is a cardiomyopathy caused by defects in the biosynthesis of the mitochondrial phospholipid cardiolipin. BTHS mouse models and cardiomyocytes derived from patient stem cells unveil the defects in respiratory chain function.